On the Foundations of Organizational Knowledge: Interview With Professor Sidney G. Winter. (April 2016) - Almeida Costa, Afonso; Workiewicz, Maciej; Szulanski, Gabriel
This interview is focused on the core ideas of Sidney Winter's work, with special emphasis on his contributions to the understanding of organizational knowledge and on synthesizing and situating those ideas in the broader context of management theory. We conducted the interview on November 6, 2011, during the Knowledge and Innovation Interest Group's pre-conference program of the Strategic Management Society (SMS) annual conference in Miami.